Intestinal acetic acid regulates the synthesis of sex pheromones in captive giant pandas - Zhang, Ming-yue; Zhang, Xiao-hui; Wang, Xue-ying; Liu, Yu-liang; An, Jun-hui; Wang, Dong-hui; Cai, Zhi-gang; Hou, Rong (Frontiers in Microbiology, 2023)
As a typical solitary animal, adult giant pandas rely on chemical signals (sex pheromones) to transmit reproductive information during oestrous. Although researchers have confirmed that the gut microbiota is related to the emission and reception of sex pheromones, there is no clear correlation between the gut microbes and the synthesis of sex pheromone of giant pandas, that is, which gut microbes and microbial metabolites are participate in the synthesis of giant panda's sex pheromone. As a mirror of gut microbiota, fecal microbiota can reflect the composition of gut microbiota and its interaction with host to some extent. The purpose of this study is to explore how the gut microbes affect the synthesis of sex pheromones in captive giant pandas by combining analysis of the fecal microbiome and metabolomics. The results of correlation and microbial function analysis show that intestinal microorganisms such as Veillonellaceae and Lactobacillilaceae are associated with the synthesis of short chain fatty acid (acetic acid) and volatile ester metabolites, such as 1-butanol, 3-methyl, acetate, acetic acid, hexyl ester and 3-hexen-1-ol, acetate, (Z). In summary, based on this study, we believe that volatile metabolites such as fecal acetate participate in the process of mate preference of captive giant pandas and affect their expression of natural mating behavior. The possible mechanism is that the gut microbes can promote the synthesis of key chemical signaling substances in perianal glands through mediated intermediate fecal metabolites, thus affecting the normal information exchange between giant pandas individuals. The results of this study have greatly enriched our understanding of gut microbes regulating the synthesis of sex pheromones in giant pandas.